2020
DOI: 10.1016/j.jmbbm.2020.103889
|View full text |Cite
|
Sign up to set email alerts
|

Anisotropic and viscoelastic tensile mechanical properties of aponeurosis: Experimentation, modeling, and tissue microstructure

Abstract: Aponeuroses are stiff sheath-like components of the muscle-tendon unit that play a vital role in force transmission and thus locomotion. There is clear importance of the aponeurosis in musculoskeletal function, but there have been relatively few studies of aponeurosis material properties to date. The goals of this work were to: 1) perform tensile stress-relaxation tests, 2) perform planar biaxial tests, 3) employ computational modeling to the data from 1 and 2, and 4) perform scanning electron microscopy to de… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
4
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(19 citation statements)
references
References 52 publications
1
4
0
Order By: Relevance
“…Since the theory of this model is linear viscosity hypothesis, it cannot fully describe the nonlinear viscoelastic behavior of various biological soft tissues ( Shetye et al, 2014 ). However, Prony series is widely used and proved to be a constitutive equation that can effectively express the viscoelasticity of materials ( Grega et al, 2020 ; Shearer et al, 2020 ; Li et al, 2021 ; Morrison et al, 2023 ). In this study, R 2 and NRMSE obtained by fitting the experimental data of stress relaxation of patellar tendon before and after treatment showed that Prony series had a good fitting effect and was suitable for this study.…”
Section: Discussionmentioning
confidence: 99%
“…Since the theory of this model is linear viscosity hypothesis, it cannot fully describe the nonlinear viscoelastic behavior of various biological soft tissues ( Shetye et al, 2014 ). However, Prony series is widely used and proved to be a constitutive equation that can effectively express the viscoelasticity of materials ( Grega et al, 2020 ; Shearer et al, 2020 ; Li et al, 2021 ; Morrison et al, 2023 ). In this study, R 2 and NRMSE obtained by fitting the experimental data of stress relaxation of patellar tendon before and after treatment showed that Prony series had a good fitting effect and was suitable for this study.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, materials testing of excised tissue samples under carefully controlled experimental environments are the current gold standard for material property estimation, despite the fact that these approaches remove the tissue from the native mechanical environment. To the best of the authors' knowledge, there have been two previously published studies that have combined materials testing and structural imaging of aponeurosis, both of which qualitatively showed a collagen-rich structure with aligned, wavy fibers [22,23]. Previous materials characterization works of aponeurosis have shown properties common to biological soft tissues such as anisotropy, nonlinearity, viscoelasticity, and heterogeneity [10,[22][23][24].…”
Section: Introductionmentioning
confidence: 99%
“…To the best of the authors' knowledge, there have been two previously published studies that have combined materials testing and structural imaging of aponeurosis, both of which qualitatively showed a collagen-rich structure with aligned, wavy fibers [22,23]. Previous materials characterization works of aponeurosis have shown properties common to biological soft tissues such as anisotropy, nonlinearity, viscoelasticity, and heterogeneity [10,[22][23][24]. Specifically, aponeurosis is highly anisotropic with a longitudinal modulus between 50-750 MPa and a transverse modulus of 0.3-100 MPa, which is greater than the approximate modulus of muscle (~0.1 MPa) and comparable to that of tendon (~1000 MPa) [22][23][24].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations